SEMI-OCCLUSIVE DRESSING FOR FINGERTIP INJURY: A CASE REPORT - Young, Andre; Dian, Teuku Arief (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2024)
Introduction: A fingertip injury is an injury to the most distal part of the fingers. Anatomically, the fingertip can be defined as the part located distal to the insertion of the flexor digitorum superficialis and extensor digitorum tendons on the distal phalanx, or the interphalangeal joint if referring to the thumb.Case Report: A male patient, approximately 40 years old, with an Allen grade III fingertip injury on the right ring finger due to a work accident, was brought to the Emergency Department. The patient was informed that he would undergo an occlusive dressing procedure with local anaesthesia. Evaluation three months after injury showed optimal improvement in both the cosmetic appearance and function of the ring finger.Conclusion: Semi-occlusive dressing may be more feasible than operative treatment because of its simple technique while still be able to give satisfactory results for the patient. However, there are several conditions where operative treatment is more preferable than conservative treatment. The patient’s preferences, existing comorbidities, and the degree of injury should always be assessed before choosing any treatment option.